Inflammatory natalizumab-associated PML: baseline characteristics, lesion evolution and relation with PML-IRIS. Issue 5 (15th November 2017) - Wattjes, Mike P; Wijburg, Martijn T; van Eijk, Jeroen; Frequin, Stephan; Uitdehaag, Bernard M J; Barkhof, Frederik; Warnke, Clemens; Killestein, Joep
Abstract : Background and objective: Natalizumab-associated progressive multifocal leukoencephalopathy (NTZ-PML) patients may show imaging signs suggestive of inflammation at diagnosis ('inflammatory PML'), reminiscent of PML-immune reconstitution inflammatory syndrome (PML-IRIS). We investigated the imaging characteristics of inflammatory NTZ-PML lesions and PML-IRIS to determine differentiating and overlapping features. Methods: We scored the presence, localisation and pattern of imaging characteristics of inflammation on brain MRI scans of inflammatory NTZ-PML patients. The imaging characteristics were followed up until the occurrence of PML-IRIS. Results: Ten out of the 44 NTZ-PML patients included showed signs suggestive of inflammation at the time of diagnosis. The inflammation pattern at diagnosis was similar to the pattern seen at PML-IRIS, with contrast enhancement representing the most frequent sign of inflammation (90% at diagnosis, 100% at PML-IRIS). However, the severity of inflammation differed, with absence of swelling and low frequency of perilesional oedema (10%) at diagnosis, as compared with the PML-IRIS stage (40%). Conclusion: Patterns of inflammation at the time of PML diagnosis and at the PML-IRIS stage overlap but differ in their severity of inflammation. This supports histopathological evidence that the inflammation seen at both stages of the same disease shares a similar underlying pathophysiology, representing the immune response to the JC virus to a variable extend.